Effects of Predisposing, Enabling, and Reinforcing Factors on the Uptake of Voluntary Counselling and Testing among Female Sex Workers in Grobogan, Central Java - Muhammad Vidi Perdana; Argyo Demartoto; Dono Indarto (Journal of Health Promotion and Behavior, 2017)
Background: Human Immunodeficiency Virus (HIV) infection is a global public health issue. Global AIDS Response Progress Reporting (GARP) reported that in 2015, about 36.7 million people worldwide suffered from HIV-AIDS in all age groups. The highest number of HIV/AIDS cases occured in East Africa and South Africa. This study aimed to examine the effects of predisposing, enabling, and reinforcing factors on the uptake of voluntary counselling and testing (VCT) among female  sex workers in Grobogan, Central Java.Subjects and Method: This was an analytical observational study with cross-sectional design. It was conducted in Grobogan, Central Java, in July 2017. A sample of 142 female sex workers  were selected for this study by exhaustive sampling. The dependent variable was uptake of VCT. The independent variables were attitude, perceived benefit, external motivation from others, and social support. The data were collected by a questionnaire and analyzed by multiple logistic regression.Results: Positive attitude towards HIV status (OR= 6.09; 95% CI= 0.968 to 38.38; p= 0.054), positive perceived benefit (OR= 10.58; 95% CI= 1.48 to 76.93; p= 0.019), external motivation (OR= 8.30; 95% CI= 1.21 to 56.82; p= 0.031), and social support (OR= 9.45; 95% CI= 1.46 to 60.83; p= 0.018), positively affected uptake of  VCT.Conclusion: Positive attitude towards HIV status, positive perceived benefit, external motivation, and social support, positively affect uptake of  VCT.Keywords: HIV, Voluntary Counselling Testing, female sex workersCorrespondence: Muhammad Vidi Perdana. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: vidihse@gmail.com. Journal of Health Promotion and Behavior (2017), 2(3): 242-256https://doi.org/10.26911/thejhpb.2017.02.03.05